Biological activity of biosynthesized silver nanoparticles from Syzygium aromaticum extract using green technology against pathogenic and antibiotic-resistant bacteria isolated from burn infections - Al- Khafaji, Ahmed A.Kadhim (Technium BioChemMed, 2025)
The global surge in antimicrobial resistance (AMR), particularly among burn associated infections, necessitates novel therapeutic approaches. Silver nanoparticles (AgNPs), especially when biosynthesized using plant extracts, have shown promising antimicrobial potential. This study aimed to biosynthesize silver nanoparticles using aqueous extract of Syzygium aromaticum (clove), characterize their physicochemical properties, and evaluate their antibacterial and antibiofilm activities against multidrug-resistant (MDR) bacterial strains. Clove extract was prepared via aqueous extraction and used for the green synthesis of AgNPs. GC-MS analysis identified eugenol (77.53%) as the major bioactive component. The biosynthesized AgNPs were characterized using UV-Vis spectroscopy, FTIR, SEM, and XRD. Antibacterial efficacy was assessed against Proteus mirabilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae using the disk diffusion method, MIC assay, and biofilm inhibition assay. The synthesized AgNPs showed a surface plasmon resonance peak at 435 nm and were predominantly spherical with diameters ranging from 38–79 nm. FTIR revealed the presence of functional groups responsible for nanoparticle reduction and stabilization. Compared to clove extract alone, AgNPs demonstrated significantly greater antibacterial activity (p < 0.05), larger zones of inhibition (17–20 mm vs. 8–11 mm), and lower MIC values (15–30 µg/mL). Biofilm inhibition was notably higher for AgNPs (68–76%) than for crude extract (25–32%). Green-synthesized AgNPs using clove extract exhibit potent antibacterial and antibiofilm properties against MDR pathogens, outperforming the crude extract. Their effectiveness is attributed to the synergistic action of phytochemicals (e.g., eugenol) and the nanoscale properties of silver. These findings support their potential as alternative antimicrobial agents for clinical use, particularly in treating resistant burn infections.